The role of organizational culture and work discipline on job performance mediated job satisfaction - Harinoto Harinoto (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, Indonesia, 2017)
The research aimes to find out the correlation between organizational culture and work discipline to work performance that is mediated by employee job satisfaction. The number of research samples as many as 50 respondents from the general section of the Malang regional secretariat. The technique of taking data using questionnaires. Analysis technique using path analysis. The result of research stated that job satisfaction becomes mediator for organizational culture and work discipline to improve employee performance. The dominant indicators of job performance are timeliness and work can be completed faster than the deadline. The dominant job satisfaction indicator is employee responsive attitude toward work. The dominant organizational culture indicator of employee aggressiveness is indicated by the hard work done by the employees. The dominant work discipline is orderly on the rules, following the terms of work, compliance with applicable regulations.